Online Identity Analysis of Public Figure Jerome Polin: Analisis Identitas Daring Tokoh Publik Jerome Polin - Artanadya, Della Rizky; Anayarahma, Ninda (Universitas Muhammadiyah Sidoarjo, 2025)
Jerome Polin is a well-known Indonesian YouTuber and content creator who often combines comedy and science in his humorous and educational videos. He has successfully built a strong and likable online persona. Through a varied content strategy and constructive audience engagement, he appears to have effectively handled the challenges of context collapse. However, he must remain aware of the dangers posed by misinformation and the potentially harmful effects of participatory surveillance. This analysis will explore how Jerome Polin has created his online identity, managed interactions with a wide range of audiences, and navigated the risks associated with online participation and privacy. The findings suggest that Jerome Polin has cultivated a successful online presence but must continue to be cautious about the risks inherent in the digital landscape. Highlights: Strategic Online Identity – Jerome Polin skillfully blends education and entertainment, making complex topics accessible while maintaining a relatable persona. Audience Engagement & Context Management – He effectively interacts with diverse audiences, balancing humor and learning while mitigating context collapse. Digital Risks & Responsibility – While successful, he must remain vigilant against misinformation and the unintended consequences of participatory surveillance. Keywords : Jerome Polin, Online Persona, Content Strategy